Epidemiology, risk factors and outcomes of bloodstream infection caused by ESKAPEEc pathogens among hospitalized children - Xiaoshan Peng; Wei Zhou; Yu Zhu; Chaomin Wan (BMC, 2021)
Abstract Background Bloodstream infection (BSI) resulting from ESKAPEEc pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp) is relevant to high mortality and economic cost. Data concerning the impact of BSI due to ESKAPEEc in pediatric population was virtually scant. Our purpose was to summarize the epidemiology, risk factors and outcomes of ESKAPEEc BSI among hospitalized children. Methods Inpatients diagnosed with BSI with definite etiology between January 2016 and December 2018 were enrolled retrospectively at the West China Second University Hospital. Data were systematically reviewed on patients' clinical characteristics and laboratory findings to ascertain independent predictors, clinical features and outcomes. Results Of the 228 patients with BSI, 174 (76.3%) were caused by ESKAPEEc (124 MDR-ESKAPEEc). Multivariate analysis demonstrated that premature and/ or low birth weight (odds ratio [OR] = 2.981, P = 0.036), previous surgery and/or trauma (OR = 5.71, P = 0.029) and source of urinary tract infection (OR = 10.60, P = 0.004) were independently associated with ESKAPEEc BSI. The independent risk factor for MRD-ESKAPEEc BSI was nosocomial infection (OR = 3.314, P = 0.037). The overall mortality rate in patients with ESKAPEEc BSI was 14.4% (25/174), and no significant difference was ascertained in mortality between MRD-ESKAPEEc and non-MRD ESKAPEEc BSI groups (13.7% vs. 11.4%, P = 0.692). In addition, previous surgery and/or trauma, thrombocytopenia, and mechanical ventilation were significant risk factors for mortality caused by ESKAPEEc BSI. Conclusions More than two-thirds of BSI among hospitalized children were caused by ESKAPEEc. Previous surgery and/or trauma, thrombocytopenia and mechanical ventilation increased the risk rate for mortality in ESKAPEEc BSI. The risk factors ascertained could assist physicians to early suspect ESKAPEEc BSI and MDR ESKAPEEc BSI.